YIELD, QUALITY AND PRESERVATION OF POTATOES WHEN USING PLANT GROWTH REGULATORS - Butov A.V.; Mandrova A.A. (Техника и технология пищевых производств)
The article deals with the results of researches on the effect of modern plant growth regulators (PGR) on yield, quality and preservation of potatoes. Field experiments were performed in 2012-2014 (storage 2012-2015) in the educational-experimental farm of the Yelets State University after I. A. Bunin, on leached chernozems of the Central Black Earth Region (Lipetskaya oblast). Studied have been the following RGR: Epin-Extra, Ecopin, Ecogel, Novosil, Zircon, Humate N/K including the controls free of drug treatment. The PGP test has been performed on two backgrounds of mineral fertilizers, namely, N60P90K60 and N90P150K120. The «Udacha» variety of potato has been used. The most effective PGR options appeared to be 3.10 - Ecopin and 5.12 - Novosil. According to the background of N60P90K60 the yield of potatoes as the result of their use amounted to 30.2 and 29.1 t/ha, respectively, against 22.9 t/ha for the 1st control variant. The starch content of the tubers has increased to 15.4 and 14.9% against 14.2% of the control. Total weight losses have decreased by of 1.1-1.0% and the incidence of the products during storage has reduced up to 1.4-1.5%, against 1.9% in the control. Advanced background of N90P150K120 fertilizer has led to the increase of potato yield in the 10 and 12 versions to 33.2-32.2 t/ha when using Ecopin and Novosil against 26.8 t/ha in the 8 control variant. The yield increase against the background of higher doses of fertilizers appeared to be less amounting to 23.0 - 20.1%, compared to 31.9 and 27.1% for N60P90K60 background. A significant yield increase for both fertilizer backgrounds when using Zircon and Ecogel PGRs has been demonstrated. In major potato production it is expedient to apply the most effective PGPs Ecopin at the dose of 60g/ha and Novosil at the dose of 200 ml/ha at recommended treatment time. The use of effective drugs leads to the increase of the yield of potatoes by 27.1-31.9% and 20.1-23.0%, increases starch content of tubers and significantly reduces losses during storage.